2010
DOI: 10.3109/09537104.2010.505308
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia inPlasmodium falciparum,Plasmodium vivaxand mixed infection malaria: A study from Bikaner (Northwestern India)

Abstract: The occurrence, relation and magnitude of thrombocytopenia in different species of malaria are not clearly defined. This study included 1,064 patients admitted with malaria to study thrombocytopenia (platelet count <150,000 /cumm) in Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) mono infection and mixed infection (Pf + Pv). The species diagnosis was done by peripheral blood film (PBF) and rapid diagnostic test (RDT). Validation by polymerase chain reaction (PCR) was done only in patients with severe thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 20 publications
7
79
0
3
Order By: Relevance
“…14 Another study done by Kochar DK et al showed only 31% patients had thrombocytopenia, this difference is because they had included both inpatients as well as outpatients suffering from malaria. 15 One other study on outpatients only by Goyal et al, showed 77% patients had thrombocytopenia. 16 Frank bleeding was present in 14 of total studied population and had both PV and PF infection, and all were pancypenic.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Another study done by Kochar DK et al showed only 31% patients had thrombocytopenia, this difference is because they had included both inpatients as well as outpatients suffering from malaria. 15 One other study on outpatients only by Goyal et al, showed 77% patients had thrombocytopenia. 16 Frank bleeding was present in 14 of total studied population and had both PV and PF infection, and all were pancypenic.…”
Section: 11mentioning
confidence: 99%
“…Study done by Kochar DK et al showed 18.18% patients had platelet count less than 20000/microlitre, and only 0.6% patients had bleeding manifestations. 15 Study done by Chetiwal R et al showed 88% patients had thrombocytopenia, and mean platelet count was 79442/ microlitre, 6.9% patient had platelet count less than 20000/microlitre, and only 2.3% patients had bleeding manifestations. 13 In this study life, threatening complications were present in 46 patients.…”
Section: 11mentioning
confidence: 99%
“…Studies have postulated that malaria should be suspected in travelers who present with fever and thrombocytopenia 34 . In malaria patients, thrombocytopenia is generally mild or moderate 13,17 , and bleeding is rare 35,36 . One study found that severe thrombocytopenia in malaria was an independent predictor of death (odds ratio (OR)=13.3, 95%CI=3.2-55.1) 37 , but this finding has been contested 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia has been associated with Plasmodium knowlesi 8 , Plasmodium falciparum 9 , Plasmodium vivax, Plasmodium ovale 10 and Plasmodium malariae infections 11 . The evidence is mixed regarding the existence of a correlation between platelet count (PC) and parasitemia [8][9][10][12][13][14] . In a systematic review, Lacerda et al found no differences in the frequency of thrombocytopenia across species of Plasmodium; the frequency of thrombocytopenia ranged from 24-94% in all studies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, severe thrombocytopenia (platelets <2 × 10 4 /mm 3 ) may be a common manifestation of vivax monoinfection 5 . Role of platelet phagocytosis has been suggested in vivax malaria 6 .…”
Section: Introductionmentioning
confidence: 99%